Soil phototroph community resilience comes from down under - Scott, Brian; Garcia-Pichel, Ferran (Frontiers in Microbiology, 2025)
IntroductionSeed banks are widely recognized as means of recovery following disturbance across diverse ecosystems, including soil. Phototrophic microbes, while common in surface soils, have not been considered within this context.MethodsWe subjected a variety of topsoil photosynthetically-driven communities (biocrusts) to severe disturbance by scalping off the surface layer, thereby exposing the undercrust. We collected samples from the biocrust layer, the undercrust layer, and again the recovering biocrust layer after a 4-month period. Samples were analyzed for biopigments (chlorophyll a and scytonemin) and 16S rRNA gene copies and its sequence diversity.ResultsRibosomal gene counts and pigment analyses revealed consistently rapid recovery, as much as 52% content in 4 months. Recovery could be traced to dormant cyanobacterial “seeds” in the undercrusts. Alternative pathways for recovery, including natural or interventional inoculation and lateral spread, did not constitute a comparable force.DiscussionOur findings bring soil phototrophs within the ecological framework linking seed banks to resilience following disturbance. The overlooked role of undercrusts in prior research invites a reinterpretation of past studies and may inform new restoration strategies.